Cybercrime Regulations in the National Criminal Code - Sitompul, Josua (UI Scholars Hub, 2025)
In early 2023, Indonesia promulgated the National Criminal Code, which will be effectively enforceable in 2026. The promulgation is considered a historical milestone in the development of Indonesia’s criminal law that has strategic consequences for the criminal justice system in Indonesia. This new code repeals criminal provisions from 29 different acts, including the Electronic Information and Transactions Act (EIT Act). Policymakers inserted and developed new concepts into the new code, one of which is the concept of cybercrime. Employing a doctrinal legal research method, this article analyses the approaches used in the new code to regulate cybercrime. The results showed that the approaches implemented in the National Criminal Code have widened the scope of cybercrime with discordances. In that regard, the article emphasises the importance of law enforcement agencies scrutinising the use of cybercrime provisions according to their purposes, and they have to address inconsistencies and disharmonious provisions found within the code to prevent overcriminalisation.